Geochemical characteristics and mining prospects of REE in Lugou coal mine of Xinmi coalfield - Luo Zhonggeng; Li Chunhui; Wang Shikui; Liang Handong (矿业科学学报, 2020)
The content of rare earth elements and their occurrence characteristics under low temperature ashing conditions in Lugou coal mine of Xinmi coalfield were studied by XRD, XRF and ICP-MS analysis techniques.The results show that the total content of rare earth elements (REE) in No.1 coal seam of Lugou coal mine is 21.85~287.62 μg/g, with a mean value of 96.20 μg/g.The rare earth elements in the coal seam show obvious light rare earth enrichment and heavy rare earth loss, which is mainly derived from terrigenous clastics.The content of rare earth elements in coal is related to the content of clay minerals in coal, and it is most closely related to the content of illite.Although the tectonic movement of the Mesozoic and Cenozoic destroys the structure of coal seams, it has no obviows effect on the content and distribution characteristics rare earth elements in coal.The content of rare earth elements in some stratification has satisfied the requirements of industrial mining, and has certain development and utilization value.